Factor Analysis of Sharia Mobile Banking Using the Utaut2 Model in Millenial Generations - Julita, Zia; Susy Suhendra, Euphrasia (International Journal of Scientific Research and Management (IJSRM), 2023)
The rapid development of technology has had an impact on a variety of fields, one of which is banking. All banks compete in making services digitally. Shariah Bank provides mobile banking app services for use by millennial-dominated customers. The aim of this research is to identify the factors that influence millennials use of mobile sharia banking using the UTAUT2 model. This research is quantitative research, where the research instrument is a questionnaire with a Google Form to obtain primary data from respondents. The population in this study is the millennials in the Jabodetabek region; the number of samples used was as high as 200 respondents. The sampling method is non-probability sampling with purposive sampling. The analytical method used is PLS-SEM. The results of this study show that performance expectancy, social influence, facilitating condition, price value, and habit influence behavioral intention. Use behavior is influenced by facilitating conditions, habits, and behavioral intentions. The conclusion of this study is that it proved that the construction of UTAUT2, consisting of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, and price value, has important roles in determining the intentions and attitudes of mobile banking use.